Enhancing Citizen Engagement in Smart Cities with Chatbot - Chung Huang; Keemo Gan (Etunas, 2023)
Smart cities rely on the engagement and participation of their citizens to achieve their goals of improving quality of life, sustainability, and efficiency. However, traditional communication channels between citizens and smart city services can be limited, leading to reduced engagement and participation. In this paper, we propose the integration of a chatbot to enhance citizen engagement in smart cities. The chatbot is designed to understand natural language queries and provide quick and accurate responses about smart city services such as public transportation, waste management, and emergency services. The chatbot is integrated with the smart city services through APIs, allowing for real-time information updates. A user study is conducted to evaluate the effectiveness of the chatbot in enhancing citizen engagement. The study measures metrics such as user satisfaction, response time, and accuracy of the chatbot's responses. The results indicate that the chatbot is effective in improving citizen engagement by providing quick and accurate information about smart city services. The integration of a chatbot has the potential to enhance citizen engagement in smart cities, leading to improved quality of life, sustainability, and efficiency. The chatbot provides a convenient and accessible communication channel for citizens to interact with smart city services, improving overall citizen experience in the city. Future work may involve expanding the chatbot's capabilities to include more smart city services and improving the chatbot's performance through machine learning algorithms.